Analisis Interpretasi Pada Karya Lukis Hatmi Negria Taruan - Sabri (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract painting by Hatmi Negria is stated as art that distorts or relates to form, in this case its essence. The object is presented in an abstraction in the form of its essence. The style or school of art initiated in its creation uses two methods of approach. The first approach is without direct reference to a form in reality. For the second approach, the imagery in this abstract power comes from nature. Something is changed to become simpler in a biomorphic or geometric form, that is the process of creating the style or flow of abstract art. Expressive is another form or way of creating it. The elements contained in the work above are arranged based on the principles of composition, namely harmony, balance and contrast so as to create an eerie, dull, worrying and terrifying atmosphere. The shape of the human figure chosen has a hidden meaning to be studied in more depth. The symbols that represent the colors chosen by Hatmi through the two works described are very close to reality, such as the colors which overall look dull, depicting the destruction of drug addicts who do not have a bright future and some end in death.